Identification of Hub Genes Related to Liver Metastasis of Colorectal Cancer by Integrative Analysis - Liu, Sicheng; Zhang, Yaguang; Zhang, Su; Qiu, Lei; Zhang, Bo; Han, Junhong (Frontiers in Oncology, 2021)
Liver metastasis of colorectal cancer (LMCRC) severely damages patient health, causing poor prognosis and tumor relapse. Marker genes associated with LMCRC identified by previous study did not meet therapeutic demand. Therefore, it is necessary to identify new biomarkers regulating the metastasis network and screen potential drugs for future treatment. Here, we identified that cell adhesion molecules and PPAR signaling pathway were significant enriched by analyzing the integrated-multiple expression profiles. Moreover, analysis with robust rank aggregation approach revealed a total of 138 differentially expressed genes (DEGs), including 108 up-expressed and 30 down-expressed genes. With establishing protein-protein interaction network, we also identified the subnetwork significantly enriching the metastasis-associated hub genes including ALB, APOE, CDH2 and ORM1. And ESR2, FOXO3 and SRY were determined as key transcription factors regulating hub genes. In addition, ADH-1, Epigallocatechin, CHEMBL1945287, and Cochinchinenin C were predicted as potential therapeutic drugs. Moreover, the antimigration capacity of ADH-1 and Epigallocatechin were confirmed in CRC cell lines. In conclusion, our findings not only offer opportunities to understand metastasis mechanism but also identify potential therapeutic targets for CRC.